How Do Effective Upper Elementary Teachers of English Language Learners Show Support?. Issue 7 (July 2019) - Banse, Holland W.; Palacios, Natalia A.; Martin, Anna
Background/Context: Latino English language learners (ELLs) comprise a rapidly growing portion of the student population, and much empirical attention has been devoted to supporting their English language and literacy proficiency. Less is known about how to support Latino ELLs' social-emotional needs. Latino ELLs face the dual challenge of learning English and academic content simultaneously; they also may face stigma, anti-immigration sentiment, and deficit perspectives from teachers and peers. Consequently, they may be in especial need of support from their teachers. Research Question: This study addresses the question, How do effective teachers show support within upper elementary classrooms with varying levels of English language proficiency? Research Design: We employed a multiple and comparative case study approach to answer this question, using videotaped English language arts lessons from the Measures of Effective Teaching data set. We compared how teachers demonstrate supportiveness in three types of fourth- and fifth-grade classrooms: (1) high-ELL and high-gains; (2) no-ELL and high-gains; and (3) high-ELL and low-gains. Conclusion/Recommendations: We observed that only high-ELL, high-gains teachers showed supportiveness in the following distinct ways: through contingent and effusive praise, by describing the relevance of content, and by advancing relationships with students. We discussed why these demonstrations of supportiveness may be important, particularly for Latino ELLs. We conclude with ideas for future research and practical implications for teachers and teacher preparation programs.